Utilização de efluente nitrificado para oxidação de sulfeto oriundos do efluente de tratamento anaeróbio de esgotos sanitários - Cabral, Luciana Leôncio Bertino (2018)
The present study had, as main objective, to evaluate the oxidation of sulfides usin g nitrified effluent as an electron acceptor in anaerobic reactors treating sanitary sewage. This process was possible because the interactions between the carbon, nitrogen and sulfur cycle that allow the practical use of the fundamentals already known about the process of denitrification and oxidation of sulfides at simultaneous moments. The experiments were perform in a Hybrid Anaerobic Reactor (HAR) with a useful volume of 60 liters and TDH of 24 hours. The HAR consists of a UASB reactor in the lower part and in the middle part an Anaerobic Filter, with polyurethane foam used as a support form. An equilibrium tank, designed at the top of the HAR, sent the effluent into an Intermittent Flux of Sand’s Filter - FaFint, allowing the formation of the nitrified effluent, with the purpose of recirculating this material to the anaerobic phase of the system. The research was developed in four phases. In the first phase, the HAR nourished with 100% of sewer from the Campina Grande – PB city, with the purpose of comparing its results with the other phases, in which different flows in each phase of the operation recirculated from the effluent produced in the FaFint. During phase 2, the HAR received a flow of 83% of sewer and 17% of nitrified effluent, in phase 3 the flow changed to 64% of raw sewer and 33% of the effluent recirculated from FaFint. While in phase 4, the ratio applied was 50% crude sewer and 50% nitrified effluent. Concentrations of sulfate, sulfide, elemental sulfur, nitrate, nitrite, organic nitrogen and ammoniacal nitrogen were monitored, as well as other parameters of interest. The results showed that the operational conditions imposed during phase 4 allowed the accumulation of 41% of the oxidized forms of sulfur in the anaerobic phase, 31% in the form of sulfate and 10% in the form of elemental sulfur. The addition of a higher amount of nitrified effluent in the HAR also favored the denitrification process, showing 38% of the nitrogen forms removed during the anaerobic stage and a 46% removal of nitrogen in the final effluent. Thus, it was concluded that the use of nitrate and nitrite can effectively treat the stinks generated by the treatment of anaerobic wastewater systems.